Schwannoma - Subba Rao Vanukuru; Vivekanandh Reddy Gangili; Jithendar Reddy Kubbi; Navadeepak Kumar Korvipati; M S Muni Sekhar (Wolters Kluwer Medknow Publications, 2012)
Schwannoma in the head and neck is usually arising from parapharyngeal space, but masseteric schwannoma is very rare. We report a schwannoma arising from masseter muscle in a 60-year-old male patient, who was presented with a history of painless swelling on the left cheek for 3 years and the mass was surgically removed from the left cheek of a 55-year-old man and pathological examination revealed schwannoma with Antoni A and B patterns, and numerous hyalinized masses (Verocay bodies) surrounded by spindle-shaped cells and was diagnosed as schwannoma.